A table of values for the equation should be completed as follows;
x y
-5 2
-3 0
-1 0
0 1
1 2
3 4
5 6
In order to use the given absolute value function y = |x + 2| - 1 to complete the table, we would have to substitute each of the values of x (x-values) into the absolute value function and then evaluate as follows;
When the value of x is -5, the absolute value function is given by;
y = |x + 2| - 1
y = |-5 + 2| - 1
y = 2.
When the value of x is -3, the absolute value function is given by;
y = |x + 2| - 1
y = |-3 + 2| - 1
y = 0.
When the value of x is -1, the absolute value function is given by;
y = |x + 2| - 1
y = |-1 + 2| - 1
y = 0.
When the value of x is 0, the absolute value function is given by;
y = |x + 2| - 1
y = |0 + 2| - 1
y = 1.
When the value of x is 1, the absolute value function is given by;
y = |x + 2| - 1
y = |1 + 2| - 1
y = 2.
When the value of x is 3, the absolute value function is given by;
y = |x + 2| - 1
y = |3 + 2| - 1
y = 4.
When the value of x is 5, the absolute value function is given by;
y = |x + 2| - 1
y = |-1 + 2| - 1
y = 6.